college math

posted by .

solve the equation
1). (x+4)(x-12)=5x


2). 4x^2+2x-14=16-17x

  • college math -

    This is an example of why we always get everything on the left side, then factor to make the product zero:

    (x+4)(x-12) = 5x
    x^2 - 8x - 48 = 5x
    x^2 - 13x - 48 = 0
    (x-16)(x+3) = 0

    Now we have a zero product. That means that if any of the factors is zero, then the product is also zero.

    So, x = -3 or 16


    Now do the same steps with the second equation

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algebra

    Solve: 5x-3=11+12x; 17x-3=11; 17x-3+3=11+3= 17x=14; x= 14/17 is this right?
  2. Math

    solve the equation 20x^3 +44x^2 -17x -5 given that -5/2 is a zero of f(x) 20x^3 +44x^2 -17x -5 I used synthetic division and got 20x^2-6x-2=0 took 2 and divided it out of that equation 2(x+5/2)=10x^2 -3x-1 then i factored it out the …
  3. Algebra 1

    solve each equation x(x - 3) - x(x+4)=17x - 23
  4. math

    Solve the following equation. (Examples 1-6) 15x2 = -17x + 4 x = 1 (smaller value) x = 2 (larger value)
  5. help in math

    solve and check each of the following quadratic equation (1) x^2=6x (2) x^2=3x (3)x^2=17x (4) x^2=5x+6 (5) x^2+9x=10
  6. algebra

    If (x-3) is a factor of 3x^3+bx^2-17x-12. a. Find the value of b. b.Hence , find the roots fo the equation 3x^3+bx^2-17x-12=0.
  7. college algebra

    how do I solve this: (17x^3-5x^2+4x-3)-(5x^3-9x^2-8x+11) and putting the resulting polynomial in standard form?
  8. Math help Steve?

    1) Given that p(-3), p(-1), and p(5)=0, which expression could be p(x)?
  9. Math

    1) Given that p(-3), p(-1), and p(5)=0, which expression could be p(x)?
  10. Math

    1) Given that p(-3), p(-1), and p(5)=0, which expression could be p(x)?

More Similar Questions